The Bias Against Dependence: Women and Passive Citizenship in the Doctrine of Right. - Rodríguez Ramírez, Jorge Omar (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Kant distinguishes between passive and active citizens; only the latter are entitled to vote. The difficulty is that he never justified this restriction, so two main theses have been proposed to explain it: the corruption thesis, which holds that passive citizens, by virtue of their dependence, lack autonomous judgment and therefore cannot vote; and the interdependent-independence thesis, which argues that the issue is not judgment but social position—those who depend on others cannot be co-legislators. This article advances a middle position: passive citizenship is a social condition of dependence, yet there is also evidence that Kant distrusted the judgment of certain groups he deemed passive, such as women. I will argue that his analysis treats dependence through a bias: the dependent are presumed unable to judge on a par with active citizens.